Post-traumatic growth trajectories and influencing factors in patients undergoing hip and knee arthroplasty: a prospective longitudinal study - Xie, Yan; Fu, Zhongmin; Li, Peifang; Chen, Jiali; Zhang, Lin; Liu, Ying; Ning, Ning; Zhou, Zongke (Frontiers in Psychiatry, 2025)
BackgroundTotal hip/knee arthroplasty (THA/TKA) has emerged as the gold-standard treatment for end-stage osteoarthritis. However, persistent postoperative pain and surgical trauma often induce psychological distress, complications that are frequently overlooked despite high procedural success rates. Leveraging Post-Traumatic Growth (PTG) theory, this study longitudinally investigated PTG levels. Through multidimensional analysis of predictive factors, we can provide an evidence-based framework for psychological interventions to accelerate rehabilitation.MethodsThis prospective longitudinal study included 160 patients undergoing joint replacement surgery for osteoarthritis (79 hip and 81 knee patients). In addition to collecting demographic and disease-related data, several assessments were conducted at four time points: preoperative day 1 (T1), postoperative day 1 (T2), postoperative month 1 (T3), and postoperative month 3 (T4). The instruments used included the Post-Traumatic Growth Inventory (PTGI), General Self-Efficacy Scale (GSES), Perceived Social Support Scale (PSSS), Medical Coping Modes Questionnaire (MCMQ), Harris Hip Score (HHS), and Knee Society Score (KSS). Univariate analysis and stratified regression were applied to explore the influencing factors.ResultsPTG scores showed a statistically significant nonlinear progression characterized by: preoperative day 1 (27.23 ± 12.87), postoperative day 1 (48.61 ± 14.49), postoperative month 1 (42.87 ± 12.72), and postoperative month 3 (64.37 ± 9.42). Housing type (T1, T2, T4), arthritis location (T1), surgical site (T2), complications (T4), comorbidities (T1), and joint function (T1–T4) were significant predictors of PTG (P < 0.05). Self-efficacy was positively correlated with PTG at T1 and T2 (P < 0.05). Coping strategies, such as “facing” (T1, T4), were positively correlated with PTG, while “avoidance” (T1, T2, T4) and “yielding” (T1) showed negative correlations (P < 0.05). Family support (T2, T3) was positively correlated with PTG (P < 0.05).ConclusionsThe PTG scores in THA/TKA patients demonstrated a curvilinear upward trajectory over time, maintaining moderate to low overall levels. Notably, the 1-month postoperative period emerged as a critical window for targeted interventions. Joint function, self-efficacy, proactive coping strategies, and social support significantly enhanced PTG levels, whereas yield-avoidant coping strategies showed negative correlations with PTG scores. Healthcare providers should monitor multidimensional factors influencing PTG variations across different time points, formulating evidence-based health education programs and personalized interventions to accelerate rehabilitation processes.